Psychopathy, Neuroticism, and Abusive Behavior in Low Risk Child Sex Offenders. Issue 8 (17th November 2019) - Stoll, Cedric B.; Boillat, Coralie; Pflueger, Marlon O.; Graf, Marc; Rosburg, Timm
ABSTRACT: Personality traits are considered as an important aspect in the assessment of child sex offenders (CSOs). The current study sought to elucidate the association between neuroticism, psychopathy, and abusive behavior in low risk CSOs. 43 pedophilic CSOs and 21 controls (CTLs) completed the NEO-Personality Inventory-Revised (NEO-PI-R), Psychopathy Checklist: Screening Version (PCL:SV), and Multiphasic Sex Inventory (MSI). Our results revealed small differences in PCL scores between CSOs and CTLs, with comparatively low levels of psychopathy in both groups. Higher levels of neuroticism were associated with higher PCL scores, in both CSOs and CTLs. However, higher PCL scores in CSOs did not correlate with higher MSI total scores on the subscale child molest . These findings suggest an ambiguous role of psychopathy in CSOs: higher levels of psychopathy co-occur with higher levels of neuroticism, but psychopathy does apparently not modulate abusive behavior, at least not in low risk offenders, as currently investigated.